Functional manufacturing and mechanical dynamics II : selected, peer reviewed papers from the 2012 international conference on functional manufacturing and mechanical dynamics, January 22-25, 2012, Hangzhou, Zhejiang, China - Guo, Hun (Trans Tech Publications, 2012)
This selection of 114 peer-reviewed papers originating from the International Conference on Functional Manufacturing and Mechanical Dynamics, held on January 22-25th 2012 in Hangzhou (Zhejiang) China, is divided into chapters covering: vibration technology, mechanical dynamics, functional manufacturing and information technology. This work will be of great interest to those working in these fields.n preparation Review from Book News Inc.: The 114 papers in this collection focus on the large areas of vibrational technology, mechanical dynamics, and functional manufacturing and information tech.
Keywords: Manufacturing processes -- Congresses.; Mechanical engineering -- Congresses.; elektronické knihy; electronic books